Proprioceptive information coded by populational sensory afferents - Tatsuya Umeda; Tadashi Isa; Yukio Nishimura (Japanese Society of Physical Fitness and Sports Medicine, 2014)
Proprioceptive information is provided to the central nervous system by discharges of a large number of primary sensory receptors in the periphery. Studies using single-fiber recordings of sensory afferents have described that various modality of sensory receptors exhibit movement-related discharges. Recent advances in a multi-channel recording technique enable us to consider the contribution of a population of sensory receptors to the encoding of proprioceptive information. Discharges of an ensemble of sensory receptors accurately represent the movement kinematics and trajectory of limbs. Detailed analyses reveal different roles for each modality of sensory receptors in the specific encoding of proprioceptive information from the forelimb among total sensory receptors. Multi-channel recording of sensory receptors affords a new experimental paradigm to explore proprioceptive population coding by sensory receptors.